Three-Dimensional Normal Facial Growth from Birth to the Age of 7 Years. Issue 4 (October 2015) - Krimmel, Michael; Breidt, Martin; Bacher, Margit; Müller-Hagedorn, Silvia; Dietz, Klaus; Bülthoff, Heinrich; Reinert, Siegmar; Kluba, Susanne
<x xml:space="preserve">Abstract</x> Background: With the advent of computer-assisted three-dimensional surface imaging and rapid data processing, oral and maxillofacial surgeons and orthodontists are enabled to analyze facial growth three dimensionally. Normative data, however, are still rare and inconsistent. The aim of the present study was to establish a valid reference system and to give normative data for facial growth. Methods: Three-dimensional facial surface images were obtained from 344 healthy Caucasian children (aged 0 to 7 years). The images were put in correspondence by means of six landmarks close to the skull base (exocanthion, endocanthion, otobasion inferius). Growth curves for 21 landmarks were estimated in the three dimensions. Results: Facial regions close to the skull base (orbit and ear) showed a biphasic growth pattern, with accelerated growth during the first year of life that subsided to a decreased and linear velocity thereafter. Landmarks on the nose, lips, and chin demonstrated either a curvilinear or a linear growth pattern. Conclusions: The rapid increase of the orbit and ear region in infancy is a secondary phenomenon to the rapid growth of the neurocranium during the first year of life. Thereafter, maxillary and mandibular growth prevails. The present study gives three-dimensional normative data for an expanded growth span between birth and childhood.